PENERAPAN SUPERVISI EDUKATIF KOLABORATIF SECARA PERIODIK UNTUK MENINGKATKAN KINERJA GURU DALAM PEMBELAJARAN DI SMP NEGERI 7 MEDAN TAHUN AJARAN 2018-2019 - Irmawati Irnawati (Universitas Dharmawangsa, 2019)
The purpose of this school action research is to determine the application of interesting learning through group studies between teachers to improve teacher performance at SMP Negeri 7 Medan. This research is in the form of School Action Research (PTS), which is a study which is a collaboration between researchers and teachers. The method used is a qualitative approach that is useful for revealing teacher difficulties in the discussion process and how to overcome these difficulties in an effort to improve teacher performance. The subjects in this study were teachers at SMP Negeri 7 Medan. The number of teachers at SMP Negeri 7 Medan is 53 teachers. Based on the research results obtained from 53 teachers of SMP Negeri 7 Medan who were the subjects in this study, the results in the first cycle were obtained 22 teachers (41.51%) who already had good performance. From the performance of cycle II that was obtained then returned to reduction and presented in a table form using the same formula as cycle I, it turns out that in the results of cycle II, 45 teachers (84.9%) had good performance, so it can be concluded that the application of group studies between teachers can improve teacher performance at SMP Negeri 7 Medan.Keywords: Collaborative Educational Supervision, Teacher Performance.